Characterization of poly (vinylidene fluoride) films for biomedical applications - Chong, Li Ji. (2010)
Since the discovery of its strong piezoelectricity in 1969, poly (vinylidene fluoride) (PVDF) has been researched on extensively. Due to its list of high-performance properties, such as its non-reactivity and high resistance to a broad range of solvents, PVDF shows potential as a good biomaterial. Its piezoelectricity is also believed to be useful to cells by enhancing their growth. The main objective of this report is to investigate how solvents of different polarity affect the characteristics of PVDF films made through solvent casting. Five solvents were selected for the study. PVDF powder was dissolved in prepared solvents ratios using ultrasonic water bath and subsequently cast as films on cleaned glass substrates. The films were then baked at 140°C in the oven and retrieved after cooling to room temperature. The structural, morphology, tensile and thermal properties of the films were characterized by Fourier Transform Infrared (FTIR) Spectroscopy, X-Ray Diffraction (XRD), Scanning Electron Microscope (SEM), Differential Scanning Calorimeter (DSC), Thermogravimetric Analysis (TGA), Microtester and Contact Angle Analyzer. From the study, hexamethylphosphoramide (HMPA) was found to produce the largest fraction of β-phase PVDF (0.610) among the rest, due to its high polarity and boiling temperature. It was concluded that higher solvent polarity produces larger fraction of β-phase PVDF.